UJI KUALITAS FISIS PENGOLAHAN LIMBAH OLI BEKAS MENJADI BAHAN BAKAR ALTERNATIF DENGAN METODE DISTILASI SEDERHANA - Khatimah, Husnul Khatimah; Hernawati, Hernawati; Rahmaniah, Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2016)
This study aims to determine the physical quality of the alternative fuel used oil waste generated by the distillation process and to know how big the resulting efficiency distillation apparatus for the purification process used oil waste . This research was conducted by first designing a simple distillation apparatus and then burning twice with such a simple distillation apparatus . After the burning process is done testing the quality of the physical form of the density, viscosity and caloric value that previously had to be done first physical quality testing on used oil with the same parameters. The results obtained for each parameter before and after distillation is to density (860-864 kg/ ) and (760-761 kg/ ); for viscosity (20°C = 0,8374176,743 Poise, 40°C = 124,445 Poise, 60°C = 15,995 Poise); and (20°C = 0,8374 Poise, 40°C = 0,7268 Poise, 60°C = 0,3273 Poise); and to the calorific value (1.483 J) and (1.542 J). The results showed that the density parameter for testing and quality standards ( specifications ) of gasoline fuel . While testing the viscosity parameters and quality standards ( specifications ) type fuel kerosene . And to the calorific value obtained does not meet the standards and quality ( specifications ) of any type of fuel , but approaching the calorific value of the fuel type of gasoline.